Fuzzy splicing systems - Karimi, Fariba; Turaev, Sherzod; Sarmin, Nor Haniza; Fong, Wan Heng (Springer International Publishing, 2014)
In this paper we introduce a new variant of splicing systems, called fuzzy splicing systems, and establish some basic properties of language families generated by this type of splicing systems. We study the “fuzzy effect” on splicing operations, and show that the “fuzzification” of splicing systems can increase and decrease the computational power of splicing systems with finite components with respect to fuzzy operations and cut-points chosen for threshold languages.